2011
DOI: 10.1007/s10147-011-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and performance status in patients with pancreatic and periampullary tumors

Abstract: The results imply that pretreatment quality of life and performance status are related concepts in patients with pancreatic and periampullary tumors. This is primarily true for the physical component of the SF-36. However, despite statistical significance, coefficients of determination (r (2) values) suggest that there are additional factors determining both quality of life and performance status in patients with pancreatic and periampullary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…A key finding is that overall QOL is different from performance status. This result has been demonstrated previously in individual studies [ 3 , 4 , 26 ], but was demonstrated here to be consistent across study populations. Similarly, the relationship between tumor response in cancer patients and QOL is weak, as reported previously in a study of 989 metastatic colorectal cancer [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…A key finding is that overall QOL is different from performance status. This result has been demonstrated previously in individual studies [ 3 , 4 , 26 ], but was demonstrated here to be consistent across study populations. Similarly, the relationship between tumor response in cancer patients and QOL is weak, as reported previously in a study of 989 metastatic colorectal cancer [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Patient well-being is also closely linked with caregiver well-being, 15, 16 particularly as patient performance status and quality of life decline over time, 17 and caregiver distress limits optimal care. 18 For family caregivers, the cumulative effects of physical, emotional, social, and economic stress, often results in their own physical illness, exacerbation of co-morbid conditions, and a greater risk of their own mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Over half of the studies ( k =10) used ECOG PS to assess FPS [1524], with four using KPS [5, 2527], one using a modified version of KPS known as the Palliative Performance Status (PPS; [28]) [29], one making use of the patient-reported National Comprehensive Cancer Network-Functional Assessment of Cancer Therapy–Kidney Symptom Index (NFKSI) [30], one using the patient-reported Performance Status Scale–Head and Neck Cancer (PSS-HNC; [31]) [32], and one cooperative group study that used a variety of FPS measures, including ECOG PS and KPS [33]. Basch and colleagues [5], in addition to using KPS to assess patient FPS, administered a patient-reported version of KPS scaled from 0 to 100.…”
Section: Resultsmentioning
confidence: 99%